2012
DOI: 10.1051/alr/2012006
|View full text |Cite
|
Sign up to set email alerts
|

Fitness of early life stages in F1 interspecific hybrids between Dicentrarchus labrax and D. punctatus

Abstract: -Inter-and intraspecific crossbreeding experiments were conducted to evaluate the aquaculture potential of hybrids in the genus Dicentrarchus, focusing on fertilisation and hatching success. The experimental design consisted of 24 controlled crosses in which individual and pooled fertilisations were made between wild D. labrax individuals (8 dams and 5 sires originating from West Mediterranean and Atlantic populations) and wild D. punctatus (6 sires). Three experiments were successively performed: (1) dams fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…The sire population appeared important to survival in sea bass, supporting recent evidence for a paternal role in increased survival of young fish (Álvarez & Garcia-Vazquez, 2011;Bang, Grønkjaer, Clemmesen, & Høie, 2006;Rideout, Trippel, & Litvak, 2004), but also other broadcast marine spawners (Styela plicata; Crean, Dwyer, & Marshall, 2013). A paternal influence was formerly shown for female hatching rate in sea bass, but not for survival (Ky et al, 2012;Saillant et al, 2001).…”
Section: Additive and Nonadditive Genetic Effectssupporting
confidence: 67%
See 2 more Smart Citations
“…The sire population appeared important to survival in sea bass, supporting recent evidence for a paternal role in increased survival of young fish (Álvarez & Garcia-Vazquez, 2011;Bang, Grønkjaer, Clemmesen, & Høie, 2006;Rideout, Trippel, & Litvak, 2004), but also other broadcast marine spawners (Styela plicata; Crean, Dwyer, & Marshall, 2013). A paternal influence was formerly shown for female hatching rate in sea bass, but not for survival (Ky et al, 2012;Saillant et al, 2001).…”
Section: Additive and Nonadditive Genetic Effectssupporting
confidence: 67%
“…Indeed, regarding survival and female sex ratio, the reciprocal hybrid crosses available in this study did not outperform the two crosses involving parental forms, with hybrid (♂NAT × ♀WEM) > parental (♂NAT × ♀NAT) > hybrid (♂WEM × ♀NAT) > parental (♂WEM × ♀WEM) . Ky et al (2012) also reported that hybrid (♂NAT × ♀WEM) outperformed parental (♂NAT × ♀NAT) for hatching rate. Asymmetric performances of F 1 crosses are commonly reported in a wide range of organisms even though-contrary to sea bass-F 1 s rarely outcompete their parents as observed in, e.g., numerous freshwater fish species (Bolnick, Turelli, Lopez-Fernández, Wainwright, & Near, 2008;López-Fernández & Bolnick, 2007;Russell & Magurran, 2006;Schrader, Fuller, & Travis, 2013).…”
Section: Darwin's Corollary In Sea Bassmentioning
confidence: 90%
See 1 more Smart Citation
“…To achieve this goal, we used different complementary approaches that collectively provided strong support for ancient introgression from the sister species D. punctatus . Despite low divergence ( d XY = 0.55%), partially overlapping range distributions, and interfertility in artificial crosses (Ky et al 2012), contemporary hybridization has not been observed in the wild between D. labrax and D. punctatus (Tine et al. 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes were then fertilised at a ratio of 5-10 spermatozoa per oocyte. The fertilisation rate was evaluated in triplicate 3 hours later according to the methodology used for seabass fertilisation rate estimation by Ky et al (2012).…”
Section: Full-sib Family Productionmentioning
confidence: 99%